Rancang Bangun Sistem Monitoring Bimbingan Skripsi Berbasis Web - Sirait, Andrio Pratama; Nasution, Salhazan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Application based on computer nowadays growth so fast on every scope. Every institute trying to improve research quality by using application based on website or mobile phone. Thesis is a term in Indonesia to describe scientific work as one of the requirements for a bachelor's degree including department of electrical engineering, University of Riau. On its way, department of electrical engineering face into some problems on the process of student thesis guidance. First problem is student and lecturer are hard to find a schedule for thesis guidance meet. Second problem is lecturer experience difficulty to monitor every students thesis progress, all this time monitoring is done manually by writing note. Third problem, thesis coordinator experience difficulty to make a recapitulation because thesis coordinator have to collect all note from the lecturers to knowing student’s thesis progress. Based on these three problems, author decide to make an application that will solve these three problems.Keywords: Student’s thesis progress monitoring, Student’s thesis online guidance, Student’s thesis development